Determination and estimation of the straight the straight line parameters with the compass coupling - Mastipanova, A.V. (Pedagogy of Higher and Secondary Education, 2006)
A combined method of interpretation of a fluent curve Itne by the line with compass coupling and determination of its parameters and calculation precision estimation was suggested by the author.